Multiple Acantholytic Acanthomas in Junctional Epidermolysis Bullosa - Sota Itamoto; Ken Natsuga; Takashi Seo; Shota Takashima; Hideyuki Ujiie (Acta Dermato-Venereologica)
Abstract is missing (Research letter)